Reaksi Pasar atas Pengumuman Dividen PT.Kalbe Farma saat Pandemi Covid-19 - Mohammad Arridho Nur Amin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
PT. Kalbe Farma is one of the issuers that earned a very large profit per share during the Covid-19 pandemic, this happened because of PT. Kalbe Farma is a supplier of medical devices and medicines needed by the community and government agencies, even during 2020 PT. Kalbe Farma can distribute dividends twice amid the Covid-19 pandemic conditions. This certainly gives a signal to investors and the public that PT. Kalbe Farma has resilience and can still increase its stock price when the economy is in recession. The purpose of this study is to see how much abnormal return and trading volume activity PT. Kalbe Farma obtained for the announcement of the second dividend in December 2020. The method used in this research is the method of studying events. The observation period was carried out in this study, which is 5 days before the dividend announcement and 5 days after the dividend announcement of PT. Kalbe Farma. The data used in the study were daily stock closing prices, daily JCI data, daily trading volume, and the number of outstanding shares. The results of the study obtained are a significant abnormal return value above 0.05 which is 0.290. The significance value of TVA is 0.380 so it can be concluded that there is an abnormal difference in return and trading volume activity before and after the announcement of pt dividends. Kalbe Farma